SOCIAL STUDIES LEARNING BASED ON LOCAL WISDOM VALUES "PANCASILA VILLAGE" LAMONGAN TO DEVELOP DEMOCRATIC ATTITUDES - Priyatno, Octavian Hendra; Pambudi, Ilham Galih (International Conference On Social Science Education, 2024)
The diversity of Indonesian society on the one hand can provide positive value for the nation if there is complementary interaction so that it has the potential for the progress of the nation itself. However, on the other hand, problems will arise if the plurality is not able to be managed properly which ends in a conflict. To build a young generation that is sensitive to social problems requires an educational program that not only provides knowledge, but also the meaning and implementation of the knowledge gained in everyday life. The purpose of this research is to develop social studies learning based on local wisdom values "Pancasila Village" Lamongan in order to foster democratic attitudes. The method used in this research includes three stages, namely: 1. preliminary study phase; 2. development study phase, and 3. evaluation phase. The results obtained: 1. The implementation of social studies learning applied by teachers, pay attention to; a) teaching and learning activities that take place in one direction, b) lack of interest in reading in each student, c) the use of learning facilities that are not yet optimal, d) the material is less contextual with everyday life, and e) teaching and learning activities are less active students. 2. The procedure used in this development uses the Borg and Gall development model. (3) Based on the analysis using two groups of classes, namely experimental and control, obtained the value of tcount> ttable (3.101> 1.711) which shows the difference in the average cognitive scores of experimental and control group students. While testing the affective domain obtained a value of tcount> ttable (2.527> 1.711).